Lagrangian numerical simulation for solid-liquid two-phase flow in a curved duct. (3rd August 2009) - Guo, Liejin; Pan, Dong; Hu, Xiaowei; Zhang, Ximin; Zhao, Liang
A multiway coupling Lagrangian model was developed and used to simulate the solid-liquid two-phase flow in a curved duct. Particle-wall collision and interparticle collision were included by hard sphere model and stochastic collision model. Comparison between experimental results and numerical simulation shows a reasonable agreement. The effects of liquid mean velocity, curvature radius and section shape of a curved duct on particle volume concentration distribution were investigated by this model and a new ideal for separation enhancement between liquid and solid was proposed.